Implementation of Green Economy and Green Acouting in International Companies - Anggraini, Avita; Handoko, Steven Nathanael; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
The aim of this study is to investigate how the Green Economy and Green Accouting can be applied in an international business context. This study uses a descriptive approach that aims to provide an objective picture of the use of the Green Economy in international business. This approach gathers valuable data to describe the relevant facts, and then generates detailed conclusions regarding the issue, event, or phenomenon being studied. The importance of the green economy is increasingly felt in the evaluation of business impacts on the environment and in encouraging sustainable business practices.